Oxidative stress biomarkers in endometrial secretions: A comparison between successful and unsuccessful in vitro fertilization cycles. (August 2016) - Rahiminejad, Mohammad Ehsan; Moaddab, Amirhossein; Ganji, Maziar; Eskandari, Nika; Yepez, Mayel; Rabiee, Soghra; Wise, Meredith; Ruano, Rodrigo; Ranjbar, Akram
Highlights: Endometrial secretions can be used a suitable samples for identification of oxidative stress biomarkers. Higher levels of oxidative stress biomarkers are observed in failed in vitro fertilization cycles. Oxidative stress biomarkers may be considered as predictors of in vitro fertilization outcome. Abstract: A potential role of oxidative stress has been implicated in the outcome of various steps of assisted reproductive technology (ART). In a prospective cohort study, a total of 100 patients undergoing IVF/ICSI procedure due to male factor infertility were recruited based on the inclusion criteria. In all patients, 1–2 ml of endometrial secretions was aspirated prior to embryo transfer. The oxidative stress markers in endometrial secretions, including superoxide dismutase (SOD), catalase (CAT) activities, lipid peroxidation (LPO), total thiol groups (TTG), and total antioxidant power (TAP) were investigated and compared among study groups including term pregnancy, failed IVF cycle, and miscarriage. P < 0.05 was considered statistically different. Of the 100 patients, 28 cases (28%) resulted in ongoing pregnancy (biochemical pregnancy followed by clinical pregnancy), 11 cases (11%) resulted in miscarriage, and 61 cases (61%), resulted in failed IVF cycle. SOD, LPO, CAT, and TAP levels in the endometrial secretions of the three groups were statistically different (P-value <0.01, <0.001, <0.001, and <0.001, respectively). TTG levels in endometrial secretion of three groups were not statistically different (P-value = 0.837). Our results indicated that higher levels of antioxidants such as SOD, CAT, or TAP, and lower levels of oxidative stress markers such as LPO in the endometrial secretions were associated with successful IVF outcome.